The Role of Forensic Expert on the Albanian Juridical Processes Focused on Minor’s Issues - Evis Garunja (Indian Journal of Forensic Medicine & Toxicology, 2021)
Adapting the legal framework to social change highlighted the necessity of expert involvement in all stages of juridical proceedings. The expertise of the psychologist during the process constitutes an important guide for a fair and right court decision on cases focused on minors. This figure facilitates a lot the work of judges on a responsible decision for the minor’s future.The article highlights some of the duties, responsibilities, and functions of the psychologist during court proceedings, how they operate in the judicial system today, how this function can be improved to support the minor, and the institutions themselves. The article highlights some of the weaknesses of this role on its reposition as a concrete and substantial part of the judicial structure to produce maximum positive effects, as well as enhancing its opportunities and facilitating process services and the minor’s future orientation in cooperation with other institutions in charge or social services